Contribution of Nadran Tradition to the Creative Economy of Cirebon (Unit Pelayanan Bahasa, Politeknik Pariwisata Bali, 2024)
Cirebon is a city in West Java Province, Indonesia, located on the north coast of Java Island. The Nadran tradition is a hereditary tradition carried out annually by Cirebon residents which is part of tourism activities. The study aims to showcase gastronomic tourism through Cirebon’s traditional foods featured in the Nadran tradition, highlighting their contribution to the creative economy. The research employed a qualitative approach, and data were collected through interviews, questionnaires, observation, and documentation studies. The key informants include representatives from the government, suppliers, workers, cultural experts, coastal communities involved in the Nadran tradition, and information technology professionals, ensuring comprehensive, field-based insights into the Nadran Tradition. The result showed that traditional culinary traditions from Nadran are one of the creative economy sectors in Cirebon, which has the potential to be developed as a creative economy sector and as an attraction for tourism. In the long run, this event has the potential to create a culinary brand that highlights Cirebon City and increases its popularity. This Nadran tradition will encourage economic growth through its implementation. Therefore, more promotion needs to be done by spreading information about the Nadran tradition.